Ketentuan Hukum bagi Pekerja dalam Perusahaan yang Tidak Melaksanakan Employee Branding - Marpaung, Hendry; Ambarwati, Mega Dewi (Media Hukum Indonesia (MHI), 2025)
Employee branding is an effective strategy to build a company's image through employees. By creating a supportive work environment and actively engaging employees, companies can strengthen their reputation in the eyes of the public. While challenges remain, the long-term benefits of employee branding make it a worthwhile investment. Employer branding is a concept that can be considered in today's business world, where companies create a comfortable working environment and feel at home and are encouraged to give their best in their performance. In essence, employer branding aims to make the company a place that is considered good to work by employees and prospective employees. One important aspect of employer branding is providing additional benefits and facilities to employees, in a comfortable working environment, employees will be more productive and contribute better